Trajectories of fear of cancer recurrence in young breast cancer survivors. Issue 2 (6th October 2021) - Schapira, Lidia; Zheng, Yue; Gelber, Shari I.; Poorvu, Philip; Ruddy, Kathryn J.; Tamimi, Rulla M.; Peppercorn, Jeffrey; Come, Steven E.; Borges, Virginia F.; Partridge, Ann H.; Rosenberg, Shoshana M.
Abstract : Background: Fear of cancer recurrence (FCR) is more intense in younger women. Because FCR is a powerful determinant of quality of life, identifying those at risk for persistently elevated FCR can inform timing of interventions. Methods: A total of 965 women with stage 0 to stage III breast cancer enrolled in the Young Women's Breast Cancer Study, a prospective cohort of women diagnosed with breast cancer at age ≤40 years, completed the 3‐item Lasry Fear of Recurrence Index. Group‐based trajectory modeling was used to classify distinct FCR patterns from baseline through 5 years post‐diagnosis. Multinomial logistic regression was used to identify patient, disease, and treatment characteristics associated with each trajectory. Results: Five FCR trajectories were identified with the majority of participants having moderate (33.1%) or high FCR (27.6%) that improved over time. A total of 6.9% participants had moderate FCR that worsened, whereas 21.7% had high FCR at baseline that remained high throughout. In the fully adjusted multinomial model, stages II and III (vs stage I) were associated with higher odds of being in the high/stable trajectory, whereas stage 0 (vs I), being financially comfortable (vs not comfortable), was associated with lower odds of being in the high/stable trajectory. White (vs non‐White) was associated with higher odds of being in a trajectory that improved over time. Conclusions: Although FCR improves over time for many young women with breast cancer, approximately one‐third had FCR that was severe and did not improve or worsened over 5 years after diagnosis. Ongoing monitoring is warranted, with early referral to mental health professionals indicated for those at highest risk for unresolved FCR. Lay Summary: Fear of recurrence is common among young women with breast cancer. The authors followed a large cohort of young women diagnosed with breast cancer when they were 40 years of age and younger, and found 5 distinct trajectories that show moderate and severe fears do not always improve over time and may require targeted mental health intervention. Abstract : Fear of recurrence is prevalent among young women with breast cancer. The authors identify 5 distinct trajectories that show moderate and severe fears do not always resolve over time and may require customized interventions.